2021
DOI: 10.26508/lsa.202101139
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA HOTAIR interacts with Y-Box Protein-1 (YBX1) to regulate cell proliferation

Abstract: HOTAIR is a long noncoding RNA (lncRNA) which serves as an important factor regulating diverse processes linked with cancer development. Here, we used comprehensive identification of RNA-binding proteins by mass spectrometry (ChIRP-MS) to explore the HOTAIR-protein interactome. We were able to identify 348 proteins interacting with HOTAIR, allowing us to establish a heavily interconnected HOTAIR-protein interaction network. We further developed a novel near-infrared fluorescent protein (iRFP)-trimolecular fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 83 publications
(155 reference statements)
2
8
0
Order By: Relevance
“…Several studies have reported that lncRNAs apply diverse molecular mechanisms to regulate a wide range of biological functions, including linking to mRNA transcription of target genes or interacting with some RNA-binding proteins directly. Here, we found that BANCR regulates the expression of CREB1 at the protein level but not at the mRNA level. Moreover, our RNA pull-down experiment revealed that BANCR may not directly interact with CREB1.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have reported that lncRNAs apply diverse molecular mechanisms to regulate a wide range of biological functions, including linking to mRNA transcription of target genes or interacting with some RNA-binding proteins directly. Here, we found that BANCR regulates the expression of CREB1 at the protein level but not at the mRNA level. Moreover, our RNA pull-down experiment revealed that BANCR may not directly interact with CREB1.…”
Section: Discussionmentioning
confidence: 59%
“…During RNA-BioID, however, we overexpressed HOTAIR to much higher levels, suggesting that the expression level of HOTAIR might be crucial to detect PRC2 and LSD1 complexes. Li et al 27 performed ChIRP-MS to identify HOTAIR-interacting proteins in whole cell lysates of HeLa cells, which express even lower amount of endogenous HOTAIR compared to MCF7. Similarly, they did not identify PRC2 or LSD1 complex subunits and attributed this to highly abundant cytoplasmic proteins masking the LC-MS/MS signal of these known interactors.…”
Section: Discussionmentioning
confidence: 99%
“… 17 The pmiRC108-L-MCP plasmid was produced by replacing the iRFP fragment iRC124 m in piRC124 m -MCP with miRC108 using restriction enzymes Nhe I and Hind III. 29 The pNS1-2*L-miRN107/pNS1-3*L-miRN107 plasmids and pmiRC108-2*L-MCP/pmiRC108-3*L-MCP plasmids with different linker lengths within the fused proteins were constructed in a similar manner to the pNS1-L-miRN107 and pmiRC108-L-MCP plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…The protein expression plasmids were generated based on mIrisFP and iRFP TriFC systems. 17,29 The fragments of miRN107 and miRC108 were produced using the pUC57-miRFP670nano plasmid (Genewiz, Suzhou) as the template. The pNS1-L-miRN107 plasmid was then generated by replacing the mIrisFP fragment mIN165 in pNS1-mIN165 with miRN107 using restriction enzymes KpnI and XbaI.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation